Endocrine Disrupting Chemicals: Epigenetic Relevance and Mechanisms - Alatsathianos, Ioannis (International Journal of Chemotherapy Research and Practice, 2018)
Genetics alone cannot thoroughly expound the environmental impact on the molecular complexity of the endocrine system. Epigenetic-induced alteration in gene expression has emerged as a way in which environmental compounds may exert endocrine effects. The environmental compounds that interfere with normal endocrine signaling are one of the largest classes of toxicants we are exposed to, on a daily basis. Epigenetic mechanisms, mainly the methylation of DNA and the modification of histones, lead to differentiated activation and deactivation of genome domains creating phenotype plasticity and divergent endocrine function among populations and individuals, as well. The issues examined in the present review are related to environmental epigenetics, and more precisely, the epigenetic-mediated modulation and relevance of endocrine disrupting chemicals, focusing on three broad aspects: 1) persistence of EDs, 2) their major hormonal effects and 3) the potential of compounds previously considered as endocrine disruptors to induce epigenetic effects. Evidence suggests that environmental exposures notably impact expression of endocrine-related genes and, thus, affect clinical endocrine outcomes.
Keywords: hormonal effect; genistein; environmental epigenetics; exposure; endocrinology; endocrine system.